The Variability in Management according to the Quantum Physic (International Journal of Scientific Research and Management (IJSRM), 2018)
The management is a process that can lead to discover the most important physic principles as the variability; and the analysis on the Schrodinger’s cat, etc. Here we focus about what a manager must face if he or she wants to go on in the management field in order to achieve goals. You are what you think and what you decide to be. Everything comes out from mind, and your thoughts generate the reality. If you want to manage the life, before you must manage yourself. To know variabilities is to understand what it’s going to happen in life. So through analysis of all variabilities we can get the best results in management. Every person must focus the fact that thoughts, words and actions must be together, with no opposition. The variability is determined by external and internal facts, it means that the inner self world influence all the results of the life. So all changes come when we are able to change our inner self world, and it’s a math result all will change around yourself. And the power of the mind is another important point that produce the attraction law, all you think but in no contradiction create the present result of life. What you think must be in positive and in focalization of real points of the life. What we ask must be not the thing to avoid but the thing must bring the best desire result we want to achieve.